Penyelewengan Aliran Pemikiran Moden: Tumpuan Terhadap Kekeliruan dan Kecelaruan Pemahaman Mereka Terhadap Isu-isu dalam Islam - Ghazali, Mohd al-Ikhsan; Ahmad Shah, Faisal (Jurnal Usuluddin, 2010)
Islamic thought discourse nowadays had witnessed the emergence of the variety of modern thought which included among them those who presents liberal and prejudice thinking in interpreting Islamic teaching such as anti hadith and liberal movement. This article discuss about their confusion and misunderstanding towards main issues in Islam and Muslim society. Their argument in supporting their views will be present and discuss convincingly with solid evidence and facts.